Application of Mangrove Tourism Eco-edu Technology Based on Local Malay Cultural Wisdom in Women Tourism Management Groups - Prima Titisari; Elfis; Fiki Hidayat; Tika Permatasari; Indry Chahyana; Sekar Saharani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Rupat Island, located in the Bengkalis Regency of Riau Province, is a designated region for the purpose of tourism development. Particularly, the North Rupat District of the island holds significance in this regard. In the process of managing tourist destinations for mangrove ecosystems and beaches in Tanjung Medang Village, the Rupat Molek Tourism Management Women's Group (KPPW) has been actively involved. However, KPPW Rupat Molek has encountered several challenges in effectively managing this tourist destination. These challenges include the limited dissemination of information about the tourist destination on online tourism promotion platforms and inadequate management of various business aspects, such as lodging accommodations, limited culinary options, and insufficient tourist game facilities. The objective of this activity is to provide education to KPPW (Kampung Pantai Penyabong Wawasan) through the implementation of Eco-edu Mangrove Tourism technology, which is rooted on the indigenous knowledge and cultural practices of the local Malay community. The methodology employed encompasses several stages, namely the preparatory phase, the production of tourism promotional materials phase, the training and technical support phase, and the monitoring and evaluation phase. The outcomes of this endeavor encompass tourism advertising materials, which manifest as websites, social media platforms, and publications that serve as introductions to mangrove tourism. The evaluation results indicated that the participants' reception of the training material was quite favorable, as they demonstrated a clear comprehension of the material delivered by the presenters. It is anticipated that this undertaking would enhance the economic conditions of the nearby neighborhood.